Implementation of Lean Methodology in IoT-Based Smart Water Dispenser for Real-Time Monitoring and Notification - Zahra, Syifa Nursabilla Mezi; Irianto, Kurniawan Dwi (Jurnal Media Computer Science, 2025)
This research develops an Internet of Things (IoT)-based Smart Water Dispenser using the Lean Methodology approach to create a real-time monitoring and notification system that is responsive to user needs. The system consists of a load cell, temperature sensor, and ultrasonic sensor integrated into a Firebase-based mobile application. Tests on 35 respondents showed an average volume sensor error of 1.89% (standard deviation 0.62%), an average notification delay of 0.92 seconds (standard deviation 0.15 seconds), and a user satisfaction score of 4.5/5. The main innovation of this research is the integration of multi-sensors with a Lean-based mobile notification system, which has proven to increase the efficiency of drinking water monitoring in public facilities. The results of this research are recommended for large-scale development and implementation in public environments. The consistent performance demonstrates that the system is highly feasible for implementation in large-scale public facilities.